GENE IDENTIFICATION AT THE INSERTION SITE OF A HIGH SALINITY TOLERANT INSERTIONAL MUTANT RICE LINE - Zannati, Anky; Widyastuti, Utut; Nugroho, Satya (Informatika Pertanian, 2018)
High salinity is one of the major abiotic stresses affecting rice production. Previously, we have identified transposonDs insertional mutant rice lines cv Nipponbare showing improved tolerant under salinity stress The objective of thisresearch was to determine the Ds insertion site in chromosomal DNA from one of the salt tolerant mutant line (170-10) and identify the genes in the proximity. A specific amplicon around 450bp from the mutant rice line 170-10 wassuccessfully isolated with TAIL PCR technique using the degenerate and a specific Ds primers. Bioinformatics analysesfound that the insertion was located in a putative CDS designated as Os11g0686500 in chromosome 11 at the 2nd exon.Two putative CDS’s within the proximity of the Ds insertion site downstream and upstream the insertion sites were alsoidentified.